The production and export of tanned leather in the capitania of Maranhão during the period of the General Company of commerce of Grão-Pará and Maranhão (1750-1779) (Ágora Journal, 2026)
In this article, we seek to understand, based on the dialogue between History and Economics, to what extent the reforms adopted during the reign of King José I affected the production and export of leather as one of the main products shipped from the port of São Luís to Lisbon during the operation of the Companhia Geral do Grão-Pará e Maranhão (1755-1779). The main interventions adopted, such as the increase in the number of factories, ships, and traders involved, although they began to take effect in the 1760s, only ensured regularity in exports more effectively from the 1770s onwards. In addition, there were fluctuations in the quantity exported and in the values in réis obtained from sales. However, it is undeniable that the economic policy adopted by the royal authorities encouraged the production of leather, especially tanned leather, which became the third most exported product from Maranhão, alongside rice and cotton during the period.
Keywords: Export; tanned leather; General Trade Company.